ANALISIS TATA LETAK TOKO DALAM BISNIS RETAIL MELALUI PENDEKATAN KONSUMEN (STUDI KASUS PRIMA FRESHMART PANDU RAYA) - Nasution, Anggi Rizki Ramadhani; Wiaryono, Argian Ananda; Ashari, Habib; Wulandari, Haryani; Pangesti, Luthfia Nanda; Husyairi, Khoirul Aziz (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2023)
The design or layout strategy is done to make a profit. In maintaining consumers and the survival of the store from its competitors, stores need to pay attention to the comfort of visitors, one of which is with an attractive store layout. Thus, a study was conducted which aimed to analyze the store layout of the buyers' decisions at the Prima Freshmart. The research method is descriptive method. Data collection techniques using observation and in-depth interviews. The results of the study show that Modern Retail uses a type of retail layout. The layout is based on providing convenience for consumers when shopping. Apart from that, good layout placement will have an impact and increase competitiveness. The advice given is the existence of clear instructions regarding the placement of goods, so that it does not confuse consumers when shopping.